Resonance and Current Relevance of IRRODL Highly-Cited Articles: An Integrative Retrospective - Dell, Debra (International Review of Research in Open and Distributed Learning, 2021)
This paper provides an integrative-retrospective analysis of highly-cited articles from past issues of the International Review of Research in Open and Distributed Learning (IRRODL). Download metrics of published articles were used to identify the top 100 downloaded IRRODL articles from 2000–2020. Publicly-available citation metrics for the top 100 articles were used to further refine the analysis and identify the top 10 most-cited IRRODL articles. These articles were then categorized into resonant themes to frame a discussion of the key topics in present-day online and distributed learning research and pedagogy. This paper is intended to provide a broad overview and will be of interest to those who are new to the field of online learning.